A sustainability analysis of environmental impact, nutritional quality, and price among six popular diets - Yacoub Bach, Lara; Jana, Bethany E.; Adaeze Egwatu, Chisom Freda; Orndorff, Corey Jane; Alanakrih, Rinad; Okoro, Joy; Gahl, Megan K. (Frontiers in Sustainable Food Systems, 2023)
Introduction Sustainable diets and their overall impact on the environment and human health have garnered global attention. Environmental impact, human nutrition, and affordability are three relevant dimensions for assessing overall sustainability of diets. Using a relative sustainability score, we compare the Mediterranean, paleo, ketogenic, vegetarian, and vegan diets, along with the World Health Organization dietary guidelines in order to evaluate which diets are most sustainable. Methods Environmental, nutrition, and price data on individual food items were collected and used to analyze diets. Using an online meal- prep program, one week's worth of meals standardized at 2,000 kilocalories per day was generated for each diet. Estimates of greenhouse gas emissions, eutrophication, land use, water withdrawals, nutritional quality, and affordability were calculated. Ultimately an overall relative sustainability score based on these metric averages were used to compare diets. Results Our model indicates that vegan, Mediterranean, and vegetarian diets are the most sustainable across all metrics while meat-heavy diets, such as the ketogenic diet, have the greatest negative environmental impact. A diet based on the World Health Organization's dietary guidelines performed poorly with regards to affordability, environmental impacts, and nutritional quality. Diets with higher nutritional quality included the vegan, paleo, and Mediterranean diets. Diets that eliminate meat were the cheapest both by total cost and by cost per gram of food. Discussion Diets with the highest overall sustainability score share a common characteristic: they all suggest that consumers committed to sustainability should prioritize ‘plant-forward' diets. In contrast, diets rich in meat and animal products perform poorly overall but especially in terms of environmental sustainability.